Candida colonization on the denture of diabetic and non-diabetic patients - Mohammad Hossein Lotfi-Kamran; Abbas Ali Jafari; Abbas Falah-Tafti; Ehsan Tavakoli; Mohammad Hossein Falahzadeh (Wolters Kluwer Medknow Publications, 2009)
Background: Oral candidiasis is a common opportunistic infection in diabetic patients. Presence of denture in the oral cavity of diabetic patients can promote Candida colonization and results in the higher incidence of oral and systemic candidiasis. The general purpose of the present study was to evaluate and compare Candida colonization in denture of diabetic patients and non-diabetic control group. Methods: In current case-control study, samples for mycological examinations were collected from the palatal impression surface of maxillary dentures from 92 edentulous patients including 46 dia-betic and 46 non-diabetic denture wearers. All samples were cultured directly on sabouraud agar me-dium and isolated colonies were counted and identified based on specific tests. Data were statistically analyzed using Mann-Whitney and Spearman correlation tests. Results: The higher density of isolated colonies was seen in diabetic group in compare with control group (P = 0.0001). There was a statistically significant correlation between the blood glucose level (P = 0.0001) and the duration of denture usage (P = 0.022) with the colonization of Candida on den-ture of diabetic patients. C. albicans was the most common isolated Candida species in both groups, though diabetic patients with dentures had more non-albicans Candida isolated from their dentures compared to non-diabetic patients. Conclusions: Mycological findings from the present study revealed that diabetes mellitus can in-crease colonization of Candida in denture and mouth. By elimination of local and systemic factors in diabetic patients and improving their oral health care, Candida colonization and the risk of oral and systemic candidiasis will be decreased.